Marital Rape and HIV Risk in Uganda: The Impact of Women's Empowerment Factors. (December 2019) - Mengo, Cecilia; Okumu, Moses; Ombayo, Bernadette; Nahar, Shamsun; Small, Eusebius
This study used Uganda Demographic Health Survey data (2011) to examine the role of women's empowerment in reducing HIV risk among married women who experienced sexual violence in Uganda. The sample size was 8, 674 ever-married women aged 15–49 years. Significant differences were revealed for marital rape, women's empowerment variables, and reducing HIV risk according to sociodemographic characteristics. Women's labor force participation partially mediated the relationship between sexual violence and reducing HIV risk, but decision making did not. Findings highlight the need for the development and implementation of policies and programs to address marital rape and reduce HIV risk within institutions of marriage.